Analisis Perilaku Peternak Dalam Pengelolaan Ternak Babi Pada Peternakan Rakyat Di Desa Tawiri - Titahena, Brian S; Tomatala, George S. J.; Ririmase, Pieter M. (Jurnal Agrosilvopasture-Tech, 2024)
This research aims to analyze the behavior of farmers in managing pigs among smallholder farmers in Tawiri village. The research variables are farmer characteristics (age, education, main job, number of family dependents), and business characteristics (livestock ownership, length of business). The main variables in this research are as follows: knowledge, attitudes, and actions towards managing pig farms. The research results show that the behavior of pig farmers at the level of knowledge in managing the business is in a good category, namely 83.33%, where pig farmers in Tawiri village have good knowledge in managing the livestock business. Meanwhile, at the attitude level, breeders in Tawiri village are in a good category with a percentage of 70%, this figure shows the positive attitude of breeders in running their business. while the level of farmer action is in the sufficient category with a percentage of 66.67%, meaning that the farmer's action is to implement various technical actions in managing the pig farming business.